Gunning material for roasting furnace material box

By using the spray feeding of coke gemstones, core-shell structure SiCC fibers and kaolin, the problem of intimate bonding of the surface of the roasting furnace is solved, and the high adhesion rate and mechanical properties are improved, extending the service life of the roasting furnace and reducing the Material consumption and workload.

CN119263856AActive Publication Date: 2025-01-07XINMI ZHENGXING REFRACTORY MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411628302.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-07
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The existing roasting furnace feeding box is not closely combined with the special clay bricks used in the carbon roasting furnace, which leads to peeling and a large rebound rate, causing waste of materials and increased workload, and refractory materials are susceptible to erosion at high temperatures. Shorten the life of the roasting furnace.

Method used

The spray feed consisting of coke gemstone, core-shell structure SiCC fiber and kaolin is used to synergize with kaolin through the unique structure of SiCC fibers to form stable mechanical anchoring and chemical bonding, improve adhesion and mechanical properties, and ensure spraying. The material is closely combined with the surface of the roasting furnace material box.

Benefits of technology

It effectively avoids peeling, improves the adhesion and mechanical properties of spraying and feeding, extends the service life of the roasting furnace, and reduces material consumption and workload.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263856A_ABST
    Figure CN119263856A_ABST
Patent Text Reader

Abstract

The invention provides a baking furnace material box gunning mix which comprises the following components in parts by weight: 68-75 parts of flint clay, 8-13 parts of S i CC fiber, 3-5 parts of kaolin and 0.5-2 parts of kyanite. The S CC fiber is of a core-shell structure, the interior of the S CC fiber is a carbon core, a shell layer is made of a silicon carbide material, the S CC fiber of the core-shell structure is a composite material composed of carbon and silicon elements, the interior of the S CC fiber is the carbon core, the exterior of the S CC fiber is wrapped with a layer of silicon material, and the unique core-shell structure is formed. The Si CC fiber with the core-shell structure can form a stable three-dimensional network structure at high temperature and has excellent mechanical properties, the Si CC fiber with the core-shell structure does not have the function of a binder, and the Si CC fiber with the core-shell structure and kaolin synergistically exert a bridge function, so that the adhesion of the gunning mix is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a gunning material for a roasting furnace material box. Background Art

[0002] Carbon roasting furnace is used to produce carbon. The working environment temperature of carbon roasting furnace is usually above 1200℃, sometimes up to 1400℃ or higher. Refractory materials need to maintain stable physical and chemical properties under such high temperature. Under long-term high temperature, the fire channel wall and the cross wall shrink and form cracks, which affect the normal use of the roasting furnace. On the other hand, due to wear, alkali metal erosion and deterioration and temperature fluctuation, the roasting furnace charge box is made of Al 2 O 3 -SiO 2 The erosion of refractory materials intensifies, resulting in local spalling, which shortens the life of the roasting furnace; it may even be forced to perform hot repairs or cold repairs in advance, causing losses.

[0003] Gunning materials are currently used to apply and repair furnace wall cracks, spalling and melt holes to improve work efficiency and reduce labor intensity. Gunning materials can quickly combine with special clay bricks for the material box to form a stable repair layer. The existing gunning materials cannot be tightly combined with the special clay bricks for the material box of the carbon roasting furnace, resulting in spalling. In addition, the existing gunning materials have a large rebound rate, and after spraying, they are prone to fail to adhere successfully and are easily bounced back or scattered to other areas. This not only causes direct waste of materials, but also requires additional cleaning work, further increasing material consumption and increasing workload. Summary of the invention

[0004] In order to solve the problems existing in the background technology, the present invention provides a gunning material for a roasting furnace charge box, which has strong adhesion and can effectively avoid the occurrence of peeling phenomenon.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] A gunning material for a roasting furnace material box comprises the following components: calculated by weight, 68-75 parts of coke gemstone, 8-13 parts of SiCC fiber, 3-5 parts of kaolin and 0.5-2 parts of kyanite; the SiCC fiber is a core-shell structure, the interior of the SiCC fiber is a carbon core and the shell layer is a silicon carbide material.

[0007] The preparation method of the SiCC fiber is as follows: S1, soaking the carbon fiber in a NaOH solution to remove impurities on the surface thereof, and then washing it with alcohol to obtain a carbon fiber with a clean surface;

[0008] S2, soaking the cleaned carbon fiber in step S1 in a nitric acid solution, ultrasonically dispersing the carbon fiber to increase active groups on the surface of the carbon fiber, and then drying the carbon fiber in a vacuum drying oven to obtain dry carbon fiber for later use;

[0009] S3, weighing a set amount of silicon powder, KCl powder and NaCl powder and mixing them to obtain a mixed powder to ensure the dissolution and reaction effect of the silicon powder in the molten salt system;

[0010] S4, cutting the carbon fiber dried in step S2, and placing the cut carbon fiber in a crucible, and embedding the carbon fiber with the mixed powder in step S3 to ensure that the carbon fiber is completely covered;

[0011] S5. Place the crucible containing the carbon fiber and the mixed powder in a tubular furnace for heating. The heating process includes a heating section, a heat preservation section and a cooling section. The temperature is lowered to room temperature in the cooling section to obtain a solid powder. The powder is cleaned and dried to obtain SiCC fibers with a core-shell structure.

[0012] In S1, the mass fraction of the NaOH solution is 4-7%, and the soaking time is 30-50 minutes.

[0013] In S2, the mass fraction of the nitric acid solution is 3-5%, the ultrasonic frequency is 20-50 kHz, and the dispersion time is 3-5 min.

[0014] In the step S3, the molar ratio of the silicon powder, KCl powder, NaCl powder and carbon fiber is 1:1:1:1.

[0015] In step S5, the temperature is raised from room temperature to 1400°C at a heating rate of 3°C / min, the temperature is kept at 1400°C for 4 hours, and the temperature is naturally cooled from 1400°C to room temperature during the temperature reduction period.

[0016] The particle size of the coke gemstone is less than 1000 μm, the mass percentage of aluminum oxide in the coke gemstone is greater than 44%, and the mass ratio of aluminum oxide to silicon dioxide in the coke gemstone is 0.85.

[0017] The particle size of the kaolin is 25-30 μm, and the mass percentage of aluminum oxide in the kaolin is greater than 46.54%.

[0018] The particle size of the kyanite is 45-50 μm.

[0019] This application has the following beneficial effects:

[0020] 1. Core-shell structure Si CC fiber is a composite material composed of carbon and silicon elements, with a carbon core inside and a layer of silicon carbide material wrapped outside, forming a unique core-shell structure. Core-shell structure Si CC fiber can form a stable three-dimensional network structure at high temperature. This structure has excellent mechanical properties. Core-shell structure Si CC fiber itself does not have the function of a binder. Core-shell structure Si CC fiber and kaolin work together to play a bridge role, improving the adhesion of the gunning material.

[0021] 2. The core-shell structured Si CC fiber and kaolin work together to act as a bridge, tightly connecting the coke gemstone to the surface of the roaster's box. Since the surface of the Si CC fiber has a certain degree of roughness and activity, it works together with kaolin to make the atoms or molecules on the surface of the coke gemstone and the roaster's box effectively interact, thus forming a strong mechanical anchoring and chemical bonding. At the same time, kaolin and Si CC fiber are combined with the materials on the surface of the roaster's box to form a stable interface layer, which helps to enhance the bonding strength between the coke gemstone and the surface of the roaster's box, and it is tightly combined with the surface of the roaster's box without peeling off during use.

[0022] 3. The core-shell structured SiCC fiber has good mechanical properties, while pyrotechnics and kaolin enhance the processing performance and stability of the gunning material. The SiCC fiber, pyrotechnics and kaolin work together to improve the mechanical properties of the gunning material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 , a comparative trend chart of the adhesion rate test data of the products obtained in Examples 1-5 of the present invention and Comparative Examples 1-4;

[0024] Figure 2 , a comparative trend chart of the compressive strength test data of the products obtained in Examples 1-5 of the present invention and Comparative Examples 1-4;

[0025] Figure 3 , a comparative trend chart of the flexural strength test data of the products obtained in Examples 1-5 of the present invention and Comparative Examples 1-4. DETAILED DESCRIPTION

[0026] The present application is further described in detail below with reference to the embodiments.

[0027] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0028] Raw material procurement situation: Coke gemstones are purchased from Zhoucun Xinlong Refractory Material Factory, with specifications of 0-1mm and model 45-a; kaolin is purchased from Shanxi Jinyu Fusion New Material Technology Co., Ltd., and blue topaz is purchased from Shijiazhuang Mayue Building Materials Co., Ltd.; carbon fiber is purchased from Jiangxi Shuobang New Material Technology Co., Ltd., silicon powder is purchased from Shandong Hanxinzun New Materials Co., Ltd. with a particle size of 200 mesh, KCl powder is purchased from Shouguang Xinshuo Chemical Co., Ltd., with item number 2869, and NaCl is purchased from Hubei Xingdongcheng Chemical Co., Ltd., with CAS number 159269-48-4.

[0029] Embodiment 1: A gunning material for a roasting furnace material box, comprising the following components: calculated by weight, 68 parts of pyrope, 8 parts of SiCC fiber, 3 parts of kaolin and 0.5 parts of kyanite; the SiCC fiber is a composite material composed of silicon carbide and silicon element, the interior of the SiCC fiber is a carbon core and the shell is a silicon carbide material. The particle size of the pyrope is 700μm, the mass percentage of aluminum oxide in the pyrope is 45%, and the mass ratio of aluminum oxide to silicon dioxide in the pyrope is 0.85; the particle size of the kaolin is 25μm, the mass percentage of aluminum oxide in the kaolin is 47%, and the mass of aluminum oxide in the kaolin is equal to the mass of silicon dioxide; the kyanite is 45μm.

[0030] The preparation method of the SiCC fiber is as follows: S1, placing the carbon fiber in a 5% by mass NaOH solution, soaking for 40 minutes, removing impurities on the surface thereof, and then washing with alcohol to obtain a carbon fiber with a clean surface;

[0031] S2, immersing the cleaned carbon fiber in step S1 in a nitric acid solution with a mass fraction of 4%, and performing ultrasonic dispersion at a frequency of 20 kHz for 3 minutes to increase active groups on the surface of the carbon fiber and improve the reaction between the carbon fiber and the silicon powder. The carbon fiber after ultrasonic dispersion is placed in a vacuum drying oven to dry to obtain dry carbon fiber for standby use;

[0032] S3. Weigh a set amount of silicon powder, KCl powder and NaCl powder and mix them to obtain a mixed powder to ensure the dissolution and reaction effect of the silicon powder in the molten salt system; the molar ratio of silicon powder, KCl powder, NaCl powder and carbon fiber is 1:1:1:1.

[0033] S4, cutting the carbon fiber dried in step S2 into small segments with a length of 60 μm, and placing the cut carbon fiber in a crucible, and embedding the carbon fiber with the mixed powder in step S3 to ensure that the carbon fiber is completely covered;

[0034] S5, placing the crucible containing the carbon fiber and the mixed powder in a tube furnace for heating, specifically including a heating section, a heat preservation section and a cooling section, the cooling section is to obtain solid powder at room temperature, the powder is washed and dried to obtain SiCC fiber with a core-shell structure. In the step S5, the heating section is heated from room temperature to 1400°C, the heating rate is 3°C / min, the heat preservation section is kept at 1400°C for 4h, and the cooling section is naturally cooled from 1400°C to room temperature.

[0035] Example 2: The difference between this example and Example 1 is that the proportion of each component is different, as follows: A roasting furnace material box gunning material, including the following components: calculated by weight, 75 parts of coke gem, 13 parts of Si CC fiber, 5 parts of kaolin and 2 parts of kyanite; the Si CC fiber is a composite material composed of silicon carbide and silicon element, the interior of the Si CC fiber is a carbon core and the shell is a silicon carbide material. The particle size of the coke gem is 900μm, the mass percentage of aluminum oxide in the coke gem is 48%, and the mass ratio of aluminum oxide to silicon dioxide in the coke gem is 0.85; the particle size of the kaolin is 30μm, the mass percentage of aluminum oxide in the kaolin is 49%, and the mass of aluminum oxide in the kaolin is equal to the mass of silicon dioxide; the kyanite is 50μm.

[0036] Example 3: The difference between this example and Example 1 is that the proportion of each component is different, as follows: A roasting furnace material box gunning material, including the following components: calculated by weight, 68-75 parts of coke gem, 10 parts of Si CC fiber, 4 parts of kaolin and 1.2 parts of kyanite; the Si CC fiber is a composite material composed of silicon carbide and silicon element, the interior of the Si CC fiber is a carbon core and the shell is a silicon carbide material. The particle size of the coke gem is 800μm, the mass percentage of aluminum oxide in the coke gem is 46%, and the mass ratio of aluminum oxide to silicon dioxide in the coke gem is 0.85; the particle size of the kaolin is 23μm, the mass percentage of aluminum oxide in the kaolin is 48%, and the mass of aluminum oxide in the kaolin is equal to the mass of silicon dioxide; the kyanite is 47μm.

[0037] Example 4: The difference between this example and Example 1 is that the preparation method of the Si CC fiber is as follows: S1, placing the carbon fiber in a 5% by mass NaOH solution, soaking for 40 minutes, removing impurities on the surface thereof, and then washing with alcohol to obtain a carbon fiber with a clean surface;

[0038] S2, immersing the cleaned carbon fiber in step S1 in a nitric acid solution with a mass fraction of 4% and performing ultrasonic dispersion at a frequency of 50 kHz for 5 minutes to increase active groups on the surface of the carbon fiber and improve the reaction rate of the carbon fiber and silicon powder. The carbon fiber after ultrasonic dispersion is placed in a vacuum drying oven to dry to obtain dry carbon fiber for standby use;

[0039] S3. Weigh a set amount of silicon powder, KCl powder and NaCl powder and mix them to obtain a mixed powder to ensure the dissolution and reaction effect of the silicon powder in the molten salt system; in the step S3, the molar ratio of the silicon powder, KCl powder, NaCl powder and carbon fiber is 1:1:1:1.

[0040] S4, cutting the carbon fiber dried in step S2 into appropriate shapes, such as cutting into small segments with a length of 70 μm, and placing the cut carbon fiber in a crucible, and embedding the carbon fiber with the mixed powder in step S3 to ensure that the carbon fiber is completely covered;

[0041] S5, placing the crucible containing the carbon fiber and the mixed powder in a tube furnace for heating, specifically including a heating section, a heat preservation section and a cooling section, the cooling section is to obtain solid powder at room temperature, the powder is cleaned and dried to obtain SiCC fiber with a core-shell structure. In the step S3, the heating section is heated from room temperature to 1400°C, the heating rate is 3°C / min, the heat preservation section is kept at 1400°C for 4h, and the cooling section is naturally cooled from 1400°C to room temperature.

[0042] Example 5: The difference between this example and Example 1 is that the preparation method of the SiCC fiber is as follows: S1, soaking the carbon fiber in a 5% by mass NaOH solution for 40 minutes to remove impurities on the surface, and then washing it with alcohol to obtain a carbon fiber with a clean surface;

[0043] S2, immersing the cleaned carbon fiber in step S1 in a nitric acid solution with a mass fraction of 4% and performing ultrasonic dispersion at a frequency of 35 kHz for 4 minutes to increase active groups on the surface of the carbon fiber and improve the reaction rate of the carbon fiber and silicon powder. The carbon fiber after ultrasonic dispersion is placed in a vacuum drying oven to dry to obtain dry carbon fiber for standby use;

[0044] S3. Weigh a set amount of silicon powder, KCl powder and NaCl powder and mix them to obtain a mixed powder to ensure the dissolution and reaction effect of the silicon powder in the molten salt system; in the step S3, the molar ratio of the silicon powder, KCl powder, NaCl powder and carbon fiber is 1:1:1:1; in the step S3, the heating section is heated from room temperature to 1400°C, the heating rate is 3°C / min, the insulation section is kept at 1400°C for 4h, and the cooling section is naturally cooled from 1400°C to room temperature.

[0045] S4, cutting the carbon fiber dried in step S2 into appropriate shapes, such as cutting into small segments with a length of 80 μm, and placing the cut carbon fiber in a crucible, and embedding the carbon fiber with the mixed powder in step S3 to ensure that the carbon fiber is completely covered;

[0046] S5. The crucible containing the carbon fiber and the mixed powder is placed in a tubular furnace for heating, which specifically includes a heating section, a heat preservation section and a cooling section. The cooling section is to obtain solid powder at room temperature. The powder is cleaned and dried to obtain SiCC fibers with a core-shell structure.

[0047] Comparative Example 1: The only difference from Example 1 is that the SiCC fibers are deleted.

[0048] The details are as follows: A roasting furnace material box gunning material includes the following components: calculated by weight, 68 parts of pyrotechnics, 3 parts of kaolin and 0.5 parts of kyanite; the particle size of the pyrotechnics is 700μm, the mass percentage of aluminum oxide in the pyrotechnics is 45%, and the mass ratio of aluminum oxide to silicon dioxide in the pyrotechnics is 0.85; the particle size of the kaolin is 25μm, the mass percentage of aluminum oxide in the kaolin is 47%, and the mass of aluminum oxide in the kaolin is equal to the mass of silicon dioxide; the kyanite is 45μm.

[0049] Comparative Example 2: The only difference from Example 1 is that kaolin is deleted.

[0050] The details are as follows: A roasting furnace material box gunning material, including the following components: calculated by weight, 68 parts of coke gemstone, 8 parts of Si CC fiber and 0.5 parts of kyanite; the Si CC fiber is a composite material composed of silicon carbide and silicon element, the interior of the Si CC fiber is a carbon core and the shell is a silicon carbide material. The particle size of the coke gemstone is 700μm, the mass percentage of aluminum oxide in the coke gemstone is 45%, and the mass ratio of aluminum oxide to silicon dioxide in the coke gemstone is 0.85; the kyanite is 45μm.

[0051] Comparative Example 3: The only difference from Example 1 is that SiCC fiber and kaolin are deleted at the same time.

[0052] The details are as follows: A roasting furnace material box gunning material includes the following components: calculated by weight, 68 parts of pyroxene and 0.5 parts of kyanite; the particle size of the pyroxene is 700μm, the mass percentage of aluminum oxide in the pyroxene is 45%, and the mass ratio of aluminum oxide to silicon dioxide in the pyroxene is 0.85; the kyanite is 45μm.

[0053] Comparative Example 4: The only difference from Example 1 is that the Si CC fiber is replaced by Si C fiber.

[0054] The details are as follows: A roasting furnace material box gunning material includes the following components: calculated by weight, 68 parts of pyrotechnics, 8 parts of SiC fiber, 3 parts of kaolin and 0.5 parts of kyanite; the particle size of the pyrotechnics is 700μm, the mass percentage of aluminum oxide in the pyrotechnics is 45%, and the mass ratio of aluminum oxide to silicon dioxide in the pyrotechnics is 0.85; the particle size of the kaolin is 25μm, the mass percentage of aluminum oxide in the kaolin is 47%, and the mass of aluminum oxide in the kaolin is equal to the mass of silicon dioxide; the kyanite is 45μm.

[0055] During gunning, the gunning material is mixed with water and cement for 10 minutes to obtain gunning slurry. The amount of water is controlled to 6% of the mass of the gunning material, and the amount of cement is controlled to 6% of the mass of the gunning material. Then, the gunning slurry is evenly sprayed on the damaged part of the refractory material using a high-pressure spray tank. The spraying thickness is controlled to 40mm and the spraying pressure is controlled to 0.6MPa. After the spraying is completed, it is sintered and solidified at a temperature of 1150℃.

[0056] Test example: Test object: Gunning materials were prepared according to Examples 1-5 and Comparative Examples 1-4.

[0057] Test content: Tests are conducted in accordance with the standard "Classification of Monolithic Refractory Materials" (GBT4513-2000). According to the relevant provisions of the standard, the test items of monolithic refractory materials include multiple aspects, including key performance indicators such as adhesion rate, compressive strength and flexural strength. In actual operation, the laboratory formulates the test plan based on the test methods of these standards or non-standard items.

[0058] Test results: See Table 1.

[0059] Table 1. Test data of the experimental example

[0060]

[0061] Result analysis: Analyze examples 1-5 and combine the data in Table 1 and Figure 1-3 It can be seen that the roasting furnace charge box gunning material prepared by the present invention has excellent adhesion (high adhesion rate) and mechanical properties (compressive strength and flexural strength).

[0062] Analyze Example 1 and Comparative Examples 1-3 and combine the data in Table 1 and Figure 1-3It can be seen that the adhesion rate test data of comparative example 1 is smaller than that of embodiment 1, the adhesion rate of comparative example 2 is smaller than that of comparative example 1, and the adhesion rate of comparative example 2 is substantially equal to that of comparative example 3, indicating that kaolin itself has the effect of enhancing adhesion / improving adhesion rate, while the SiCC fiber with a core-shell structure itself does not have the effect of enhancing adhesion, and the SiCC fiber with a core-shell structure can synergistically play a bridging role with kaolin to tightly connect the coke gemstone to the surface of the material box of the roasting furnace, thereby synergistically improving the adhesion / adhesion rate of the prepared roasting furnace material box gunning material.

[0063] Analyze Example 1 and Comparative Examples 1-4 and combine the data in Table 1 and Figure 1-3 It can be seen that the addition of SiC fibers can improve the compressive strength and flexural strength of the roasting furnace charge box gunning material; the use of SiC fibers made into the SiCC fibers of the shell structure of the present invention can further improve the compressive strength and flexural strength of the roasting furnace charge box gunning material; the addition of kaolin can also improve the compressive strength and flexural strength of the roasting furnace charge box gunning material; and there is a synergistic effect between SiCC fibers and kaolin, which can synergistically improve the compressive strength and flexural strength of the roasting furnace charge box gunning material.

[0064] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0065] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A roasting furnace charge box gunning material, characterized in that: The invention comprises the following components by weight: 68-75 parts of pyrope, 8-13 parts of SiCC fiber, 3-5 parts of kaolin and 0.5-2 parts of kyanite; the SiCC fiber is a core-shell structure, the interior of the SiCC fiber is a carbon core and the shell layer is silicon carbide.

2. The roasting furnace charge box gunning material according to claim 1, characterized in that: The preparation method of the SiCC fiber is as follows: S1. Soaking the carbon fiber in a NaOH solution to remove impurities on its surface, and then washing it with alcohol to obtain a carbon fiber with a clean surface; S2, soaking the clean carbon fiber obtained in S1 in a nitric acid solution, ultrasonically dispersing, and drying to obtain a dry carbon fiber; S3, weighing a set amount of silicon powder, KCl powder and NaCl powder, mixing them to obtain a mixed powder; S4, cutting the dried carbon fiber obtained in S2, placing the cut carbon fiber in a crucible, and embedding the carbon fiber with the mixed powder obtained in S3 to ensure that the carbon fiber is completely covered; S5. Place the crucible containing the carbon fiber and the mixed powder in a tubular furnace for heating. The heating process includes a heating section, a heat preservation section and a cooling section. The temperature is lowered to room temperature in the cooling section to obtain a solid powder, which is then cleaned and dried to obtain SiCC fiber.

3. The gunning material for the roasting furnace charge box according to claim 2, characterized in that: In S1, the mass fraction of the NaOH solution is 4-7%, and the soaking time is 30-50 minutes.

4. The gunning material for the roasting furnace charge box according to claim 2, characterized in that: In S2, the mass fraction of the nitric acid solution is 3-5%, the ultrasonic frequency is 20-50 kHz, and the dispersion time is 3-5 min.

5. The gunning material for the roasting furnace charge box according to claim 2, characterized in that: In S3, the molar ratio of the silicon powder, KCl powder, NaCl powder and carbon fiber is 1:1:1:

1.

6. The gunning material for the roasting furnace charge box according to claim 2, characterized in that: In S5, the temperature is raised from room temperature to 1400°C at a heating rate of 3°C / min, the temperature is kept at 1400°C for 4 hours in the temperature-keeping section, and the temperature is naturally cooled from 1400°C to room temperature in the temperature-lowering section.

7. The gunning material for a roasting furnace tank according to claim 1, characterized in that: The particle size of the coke gemstone is less than 1000 μm, the mass percentage of aluminum oxide in the coke gemstone is greater than 44%, and the mass ratio of aluminum oxide to silicon dioxide in the coke gemstone is 0.

85.

8. The gunning material for a roasting furnace tank according to claim 1, characterized in that: The particle size of the kaolin is 25-30 μm, and the mass percentage of aluminum oxide in the kaolin is greater than 46.54%.

9. The gunning material for a roasting furnace tank according to claim 1, characterized in that: The particle size of the kyanite is 45-50 μm.

Citation Information

Patent Citations

  • Low-temperature pipeline spray coating material

    CN103755374A

  • Porous corundum aggregate with core-shell structure and preparation method thereof

    CN104402466A

  • Monolithic refractory for blast furnace trough

    JP2016150854A

  • Heat-insulating coating liquid, heat-insulating material, and composition for heat-insulating coating liquid

    JP2016196387A